Penegakan Hukum Tindak Pidana Kekerasan Dalam Rumah Tangga Kepada Istri Berdasarkan Undang - Undang No. 23 Tahun 2004 Tentang Penghapusan Kekerasan Dalam Rumah Tangga: (Studi Kasus di Polres Mojokerto) - Mochamad Ryo Anharum; Rachmat Ihya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Household is the smallest part of a relationship that exists in society. Families formed within the bonds of marriage norms aim to form harmonious relationships. In fact, not all household is harmonious. The emergence of problem is often resolved in an unethical way, by using violence. Domestic Violence is efined as various forms of violence or threats of violence (physical, psychological, emotional, sexual, and neglect) to control their family members. To arrange the increase of Domestic Violence, the government make Act No. 23 of 2004 which specifically arrange the removal of Domestic Violence, as